NANOS2 interacts with the CCR4-NOT deadenylation complex and leads to suppression of specific RNAs - Suzuki, Atsushi (National Academy of Sciences, 2010)
Nanos is one of the evolutionarily conserved proteins implicated in germ cell development. We have previously shown that NANOS2 plays an important role in both the maintenance and sexual development of germ cells. However, the molecular mechanisms underlying these events have remained elusive. In our present study, we found that NANOS2 localizes to the P-bodies, known centers of RNA degradation that are abundantly accumulated in male gonocytes. We further identified by immunoprecipitation that the components of the CCR4-NOT deadenylation complex are NANOS2-interacting proteins and found that NANOS2 promotes the localization of CNOT proteins to P-bodies in vivo. We also elucidated that the NANOS2/CCR4-NOT complex has deadenylase activity in vitro, and that some of the RNAs implicated in meiosis interact with NANOS2 and are accumulated in its absence. Our current data thus indicate that the expression of these RNA molecules is normally suppressed via a NANOS2-mediated mechanism. We propose from our current findings that NANOS2-interacting RNAs may be recruited to P-bodies and degraded by the enzymes contained therein through NANOS2-mediated deadenylation.